Characterization of Poda Thurpu cattle: A native livestock population of Telangana State - K K Siripurapu; S Das; S Sharma; V R Akinepalli; M Reddy; V Yadav (Journal of Livestock Biodiversity, 2025)
India is home to approximately 1.4 billion cattle population, however, systematic process of characterization of around 70 percent of the indigenous livestock population of the country has not been carried out. Therefore, they are considered as yet undefined populations. Poda Thurpu, a yet undefined cattle population had been identified in the Indian state of Telangana for systemic characterization and registration. An estimated 15076 (approx.) cattle heads of Poda Thurpu cattle are present in the state. A sample of 3997 (approx.) from 101 breeder herds have been selected from four Mandals of Nagarkurnool District of Telangana for the purpose. Data pertaining to the physical characters, biometric and performance (dairy and draught) was collected following the format prescribed by NBAGR and analyzed. Results suggest that Poda Thurpu cattle could be classified as a distinct breed, under the draught cattle group.